A comparative study of ultrasonographic evaluation of vaginal bleeding in pregnancy with clinical examination - K. K., Sumathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ultrasound helps in assessing the type of abortion. Life threatening emergency like ectopic pregnancy, when evaluated by ultrasound gives scope for conservative approach without affecting the fertility status. The objective of this study was to compare the utility of ultrasound with clinical examination findings in pregnant females having vaginal bleeding. Methods: A hospital-based prospective study was conducted among 100 pregnant patients who have the problem of bleeding. A complete general physical and pelvic examination was done, and patients were then subjected to ultrasound examination. Epi info 7 software was used for statistical analysis. Chi- square test was used as the test of significance and correlation in terms of sensitivity, specificity was seen. P<0.05 is considered statistically significant. Results: 72 cases were diagnosed by ultrasonography as viable pregnancies with sensitivity, specificity negative predictive value (NPV), and positive predictive value (PPV) of 82% and 28 cases were diagnosed as non-viable pregnancies by ultrasonography with sensitivity of 52%, specificity of 81%, and NPV of 72%. The clinical diagnosis had sensitivity of 82%, specificity of 52%, and PPV of 40% in diagnosing viable pregnancies. In diagnosing non-viable pregnancies, clinical diagnosis had a very poor statistical correlation with sensitivity of 52%, specificity of 81%, PPV of 64%, and NPV of 72%. Conclusions: Judicious utilization of ultrasonography and a close connection with the sonologist is necessary. However, it should be realised that ultrasound is complementary in the pelvic examination and cannot substitute obstetric history and clinical examination.